Kekuatan Hukum Pembuktian Sertifikat Hak Milik Atas Tanah (Studi Kasus Putusan Pengadilan Negeri Rote Ndao Kelas II Nomor: 10/PDT.G/2022/PN RNO) - Therik, Abigail Amelia; Jacob, Yossie M Y; Dju Bire, Chatryen M (Artemis Law Journal, 2025)
Land has an important role in human survival. To ensure legal certainty and protection for each person holding the relevant rights, it is necessary to prove ownership of land rights, namely Certificate of Ownership. But in fact, even land that has been certified can still be sued. This shows that the existence of land certificates has not fully guaranteed legal certainty and legal protection to the relevant right holders as in Decision Number: 10/Pdt.G/2022/PN Rno. This research is normative juridical research with a statutory approach, case approach and conceptual approach. The results of this research show: (1) That the Plaintiff in all the evidence that has been submitted cannot dispute the validity of the Certificate of Title Number: 537 of 2009 in the name of the Defendant, dated July 27, 2009, so that the Defendant's ownership of the disputed land is valid according to the law and the Certificate of Title has strong evidentiary power that is legally binding which has been reviewed according to the theory of evidence. (2) That the panel of judges examining and adjudicating this case has given a decision based on legal considerations that have the value of justice (ex aequo et bono) and contain legal certainty. In this case, the panel of judges decided that the Plaintiff's claim was rejected in its entirety and that the Defendant was entitled to the disputed land based on Certificate of Title Number: 537 of 2009 in the name of the Defendant, dated July 27, 2009.